Fragmented urban areas: Can plants encourage birds in Jambi City urban space?. Issue 1 (November 2021) - Novriyanti, N; Ihsan, I; Irawan, B; Wulan, C
Abstract: This study aims to estimate the extent to which vegetation can encourage the presence of birds in the urban city area. Forest area, urban plantation, grove area, and residential area are The Muhammad Sabki Urban Forest location for bird and plant observed in some circular plots (r=25 m) in the morning and afternoon. Bird directly and identified using a field guide and marked plant species immediately identified using the Plantamor website. The data were analyzed using the Shannon-Wiener Index (H'), The Margalef Index (Dmg), and some using Correlative and regression analysis with IBM SPSS Statistics 28. The results obtained 23 species and a total of 534 individual birds from all observed urban space habitats. All Shannon-Wiener Index (H') values in each studied habitat type showed a moderate diversity level and low species richness (Dmg). There are 22 plant species that have been identified as places of bird activity. Correlation analysis of the number of plant species on bird species and the number of bird species on bird individuals shows a strong relationship. However, regression analysis shows that the partially analyzed variables have no significant effect, so additional values are needed from other factors.